Crossing Languages to Play with Words. Multidisciplinary Perspectives - Goth, Maik; Knospe, Sebastian; Onysko, Alexander (De Gruyter, 2016)
Wordplay involving several linguistic codes is an important modality of ludic language. This volume offers a multidisciplinary approach to the topic, discussing examples from different epochs, genres, and communicative situations. The contributions illustrate the multi-dimensionality, linguistic make-up, and the special interactive potential of wordplay across linguistic and cultural boundaries, including the challenging practice of translation.
English
Keywords: Wordplay Plurilingualism Language Contact Translation